Serum CC chemokine ligand-18 predicts lung disease worsening in systemic sclerosis - Tiev, K P; Hua-Huy, T; Kettaneh, A; Gain, M; Duong-Quy, S; Tolédano, C; Cabane, J; Dinh-Xuan, A T (The European respiratory journal, 2011)
Elevated serum CC chemokine ligand (CCL)18 reflects lung fibrosis activity in systemic sclerosis (SSc) and could be an early marker of lung function worsening. Therefore, we sought to evaluate whether serum CCL18 levels at baseline could predict worsening of lung disease in SSc. In this prospective study, 83 SSc patients were analysed longitudinally over a 4-yr observation period for the risk of occurrence of combined deleterious events, defined as a 10% decrease from baseline of total lung capacity or forced vital capacity % predicted, or death, according to serum CCL18 at inclusion. Receiver operating characteristic (ROC) curve analysis was performed for prediction of events during the first year after inclusion. The best cut-off level of serum CCL18 for prediction of a combined event within the follow-up period was 187 ng · mL(-1), with 53% sensitivity and 96% specificity (area under the ROC curve 0.86; p < 0.001). After a mean ± SD follow-up of 33.7 ± 10.8 months, a higher rate of disease progression occurred in the group with serum CCL18 levels >187 ng · mL(-1). The adjusted hazard ratio was 5.36 (95% CI 2.44-11.75; p < 0.001). In summary, serum CCL18 is an accurate predictive biomarker for the identification of patients with a higher risk of subsequent scleroderma lung disease worsening.